Pengaruh Penerapan Akuntansi Manajemen pada Rumah Sakit terhadap Perencanaan dan Pelaporan Pajak - stefanie joalim; Grescellin Elleicea; marcia devana; Michelle Pratiwi; tifanie ng (Jurnal Riset Bisnis dan Ekonomi Digital, 2026)
This research aims to learn how management accounting in the operational activities of Royal Prima Hospital affects the tax reporting. A quality management accounting is very essential in decision making by the manager. Management accounting is a branch of accounting that provides the user moneter and non-moneter data. Managers make decisions according to the data from management accounting. If the data from management accounting is not accurate, managers will make wrong decisions that will affects the operational of the hospital. As a business, hospital have to reduce as much expense as they could in order to gain more. And one of the expenses is tax. More operational expense means more tax. Therefore, management accounting indirectly relates to tax reporting. This research is a case study. Questionnaires and interviews have been carried out to gain the information in order to support our data. Based on the results of this research, we found out that quality management accounting helps to avoid the obstacles in tax planning and reporting, which also improves the efficiency in financial decision making.